1992
DOI: 10.1128/jvi.66.11.6563-6571.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a baculovirus gene encoding a small conotoxinlike polypeptide

Abstract: We identified a gene of Autographa californica nuclear polyhedrosis virus (AcMNPV) that encodes a small cysteine-rich polypeptide which has size and sequence similarity to omega-conotoxins, a class of calcium ion (Ca2") channel inhibitors, found in the venom of cone snails. Transcriptional analysis indicated that the 159-bp open reading frame, which we named cdl, and a downstream 984-bp open reading frame are transcribed as a single 1.3-kb bicistronic late RNA. The mature ctl gene product was identified as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…e ctx gene was initially found in AcMNPV with a conserved structure similar to omega-conotoxins from cone snails (Eldridge et al, 1992). Despite substantial homology between BmNPV and AcMNPV, we did not detect the ctx sequence in the BmNPV genome.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…e ctx gene was initially found in AcMNPV with a conserved structure similar to omega-conotoxins from cone snails (Eldridge et al, 1992). Despite substantial homology between BmNPV and AcMNPV, we did not detect the ctx sequence in the BmNPV genome.…”
Section: Discussionmentioning
confidence: 64%
“…e AcMNPV ctx gene was identified as a small cysteine-rich polypeptide (53 aa). Its size and sequence are similar to omega-conotoxins, a class of calcium ion channel inhibitors found in the venom of cone snails (Eldridge et al, 1992). Transcriptional assays and product purification of the ctx gene by highpressure liquid chromatography fractionation demonstrated that ctx was expressed during the baculovirus infection, but the biological role for ctx in AcMNPV infection remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Cfdef99 (iap-4, 114 nt) was significantly shorter than op106 (iap-4, 357 nt). Neonate or late instar S. frugiperda larvae infected with a wild-type AcMNPV or a ctl-1 knockout mutant, showed no differences in mortality, motility or weight gain suggesting ctl-1 is not an essential gene (Eldridge et al, 1992). AcMNPV has a ctl-1, OpMNPV and LdMNPV have ctl-1 and ctl-2 while CfDEFNPV lacks both.…”
Section: Cfdefnpv Gene Contentmentioning
confidence: 98%
“…For that reason, we named this gene ctl-2 (Table 1). OpMNPV also harbours the ctl-1 gene, which has high levels of similarity to the ctl gene of AcMNPV (Eldridge et al, 1992). The ctl gene is also present in the genome of other NPVs, GVs and entomopoxviruses.…”
Section: Auxiliary Genesmentioning
confidence: 99%